Association of propionate with coronary artery disease in a large cross-sectional study. (3rd October 2022) - Pagonas, N; Sasko, B; Seibert, F; Ritter, O; Babel, N; Westhoff, T
Abstract: Background: Microbiome has been linked to the pathogenesis of coronary artery disease (CAD) but data providing direct evidence for an association of short-chain fatty acids (SCFA) like propionate with CAD are lacking. Purpose: To study the association of propionate in blood samples with the presence of CAD Methods: This was a cross-sectional study enrolling patients admitted to invasive coronary angiography in a university hospital in Germany. Patients were prospectively recruited between from March 2017 to January 2020. Patients with known or suspected CAD and risk factors for cardiovascular diseases were screened for eligibility to participate in the trial. Main exclusion criteria were inflammatory/rheumatic disease, active cancer disease and acute infection. Blood sampling was performed after overnight fasting and before invasive procedures. Measurement of propionate was performed though liquid chromatography. Results: The study included 691 patients (median n [IQR] age, 69 [60–78] years; 406 men [59%]). A total of 368 had invasively confirmed CAD with at least one coronary artery stenosis ≥50% and 323 had non CAD and 194 had invasively excluded CAD. 129 additional patients without suspicion for CAD and without diabetes/smoking were also recruited in the no CAD group. CAD patients had significant lower levels of propionate (median) 6.08 μM (IQR, 4.31–7.65) compared to the no CAD groups 6.92 μM (4.89–9.25, <0.05). Linear regression multivariate analysis adjusted for age, gender, body mass index, hypertension, smoking, diabetes and hyperlipidemia revealed an odds ratio of 0.92 (CI 0.89–0, 96, p<0.001) for propionate as predictor of CAD. Conclusions: The study provides large-scale data for a protective role of propionate in the development of CAD, independent of the presence of other known cardiovascular risk factors. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Internal Grant, Medical School of Brandenburg